Presenting clinical and imaging features of patients with clinically amyopathic interstitial lung disease associated with myositis-specific autoantibodies - Tzilas, Vasilios; Tzouvelekis, Argyrios; Sotiropoulou, Vasilina; Panopoulos, Stylianos; Bouros, Evangelos; Avdoula, Eleni; Ryu, Jay H.; Bouros, Demosthenes (Frontiers in Medicine, 2024)
Background Lung involvement in the context of idiopathic inflammatory myopathies has significant impact on outcome; early and accurate diagnosis is important but can be difficult to achieve. In particular, patients without clinically evident muscle involvement pose a significant diagnostic challenge. Methods A computer-assisted search was conducted to identify patients with amyopathic interstitial lung disease associated with the presence of myositis-specific autoantibodies. Medical records and chest imaging studies were reviewed to identify clinical and radiologic features at presentation. Results Of the 35 patients with amyopathic interstitial lung disease associated with myositis-specific autoantibodies, the median age was 65 years (range 43–78) and 20 were women (57%). Of the patients, 34% had previously visited the rheumatology department. Presenting symptoms consisted of dyspnea (94%), cough (43%), and arthritis (23%). Raynaud phenomenon, “mechanic hands,” Gottron papules, and inspiratory crackles were present in 23, 31, 9, and 74% of patients, respectively. After a detailed history, none of the patients reported muscle weakness, while four (11%) exhibited increased CK levels; of these four, two had a concomitant increase in aldolase levels. Median FVC was 79% predicted (range: 49–135) and median DLco was 50% predicted (range: 17–103). HRCT pattern was suggestive of an alternative to UIP pattern in 31/33 (94%) patients; the most common imaging patterns were NSIP (49%) and NSIP/OP (39%). Conclusion In patients with NSIP and NSIP/OP pattern, the presence of amyopathic interstitial lung disease associated with myositis-specific autoantibodies should be considered even in the absence of clinical evident myositis.